2017
DOI: 10.1007/s00122-017-2894-4
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spatial trends in sorghum breeding field trials using a two-dimensional P-spline mixed model

Abstract: Key message A flexible and user-friendly spatial method called SpATS performed comparably to more elaborate and trial-specific spatial models in a series of sorghum breeding trials.AbstractAdjustment for spatial trends in plant breeding field trials is essential for efficient evaluation and selection of genotypes. Current mixed model methods of spatial analysis are based on a multi-step modelling process where global and local trends are fitted after trying several candidate spatial models. This paper reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
121
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 62 publications
5
121
2
7
Order By: Relevance
“…Through the analysis of simulated wheat data sets we showed that the estimates of genetic effects can be improved by accounting for spatial dependency in trials irrespective of the magnitude of the spatial variation. This is in line with the other studies (Elias et al, 2018;Rodríguez-Álvarez et al, 2018;Velazco et al, 2017;Piepho et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Through the analysis of simulated wheat data sets we showed that the estimates of genetic effects can be improved by accounting for spatial dependency in trials irrespective of the magnitude of the spatial variation. This is in line with the other studies (Elias et al, 2018;Rodríguez-Álvarez et al, 2018;Velazco et al, 2017;Piepho et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…The S2D is probably being able to better compensate for some of the local control of more advanced experimental designs. The flexibility of this type of spatial adjustment has been positively assessed in other studies where spatial variability patterns were modeled (Stefanova et al, 2009: Velazco et al, 2017; van Eeuwijk et al, 2018). Finally, the ranking of the experimental designs was consistent across different levels of noise that generate different heritabilities (i.e., from 0.58 to 0.86; Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, modeling spatial correlations might be necessary to improve genotypic effect estimation even after a good experimental design is used (Federer, 1998; Qiao et al, 2000; Campbell and Bauer, 2007; Casler, 2015; Borges et al, 2019). Several approaches have been proposed to control spatial variability such as nearest‐neighbor adjustment (Katsileros et al, 2015), smoothing techniques including penalized splines analysis (Stefanova et al, 2009; Piepho and Williams, 2010; Velazco et al, 2017), modeling the variance–covariance matrix of spatial correlations using geostatistical components (Williams, 1986; Williams et al, 2006; Piepho and Williams, 2010), or using mixed models (Smith et al, 2005). In mixed models, one‐ or two‐dimensional models are used to control spatial heterogeneity with two‐dimensional models outperforming one‐dimensional models in terms of the genotypic effects estimation (Cullis and Gleeson, 1991, Kempton et al, 1994, Piepho and Williams, 2010).…”
mentioning
confidence: 99%
“…Precise phenotypic data of the training population is a prerequisite for improving the accuracy of predicting untested genotypes in genomic selection models (Velazco et al, 2017). However, GE interactions are known to increase with increasing number of genotypes and environments.…”
Section: Introductionmentioning
confidence: 99%
“…The sheer large number of genotypes tested in early breeding stages means that experimental plots are large hence leading to local heterogeneity within experiments. To further improve prediction accuracies, different spatial adjustment models have been fronted to help deal with heterogeneity in experiments especially in these large early stage breeding trials (Lado et al, 2013; Bernal-Vasquez et al, 2014; Piepho et al, 2015; Velazco et al, 2017; Ward et al, 2019). Multidisciplinary teams are therefore continually working to improve the precision of measuring the phenotypes of the training populations to improve predictive ability of genomic selection in plant breeding, as summarized by Ward et al (2019).…”
Section: Introductionmentioning
confidence: 99%